Accounting for the multiple sources of inflation: An agent-based model investigation - Leonardo Ciambezi; Mattia Guerini; Mauro Napoletano; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
In this work, we develop a macroeconomic agent-based model to study the role of demand and supply factors in the determination of inflation dynamics. The model is characterized by local interactions of heterogeneous firms and households in the labor and goods markets. Imperfect information implies that market selection is imperfect, as it does not depend only on relative prices but also on firm size. We show that our model is able to generate realistic inflation dynamics, as well as a non-linear Phillips curve in line with the empirical evidence. We then find that the traditional demand-led explanation of inflation stemming from a tight labor market only holds when markets are competitive and efficient. Finally, we study the response of inflation to shocks impacting on consumption, labor productivity or energy costs. The results show that only demand shocks lead to wage-led inflation surges. Productivity shocks are entirely passed-through to prices without affecting the income distribution. Energy shocks, instead, induce sellers' inflation after changes in both firms' cost structure and profit margins. This is in line with the recent empirical evidence for the Euro Area.
Keywords: E31; E32; C63; 330; Inflation; agent-based models; market structure; mark-up rates; sellers' inflation